PENGARUH GAYA HIDUP, ATRIBUT PRODUK DAN KUALITAS LAYANAN TERADAP KEPUTUSAN PEMBELIAN PADA TOKOPEDIA - Nora Pitri Nainggolan; Tiurniari Purba; Heryenzus Heryenzus (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
The purpose of this study is to find out how lifestyle, product attributes, and service quality affect purchasing decisions at Tokopedia. In this study, the number of consumer respondents taken was 100 respondents as the research population using a questionnaire data collection technique. The data quality test in this study uses the validity and reliability test, the classical assumption test and the influence test in this study using multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis testing in this study uses (t test) and (f test) using SPSS software program version 25. The results of the coefficient of determination (R2) obtained from lifestyle, product attributes and service quality variables have an effect 0.496 (49.6%). The results of multiple linear regression shows that Lifestyle has an effect 0,496 (49,6%) on purchasing decisions, and product attributes has the effect 0,3968 (39,7%) on purchasing decision, and the quality of service has an effect 0,2000 (20)% on purchasing decision.. From the t test and f test, it can be concluded that lifestyle, product attributes, and service quality has a partially significant effect on purchasing decisions. From the results of the study it can be shown that lifestyle, product attributes and service quality simultaneously influence purchasing decisions at Tokopedia.